已知:A=B=7a²-7ab,且B=-4a²+6ab=7,则A=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 04:42:20
已知:A=B=7a²-7ab,且B=-4a²+6ab=7,则A=已知:A=B=7a²-7ab,且B=-4a²+6ab=7,则A=已知:A=B=7a²-
已知:A=B=7a²-7ab,且B=-4a²+6ab=7,则A=
已知:A=B=7a²-7ab,且B=-4a²+6ab=7,则A=
已知:A=B=7a²-7ab,且B=-4a²+6ab=7,则A=
7
A+2B=7a -7ab B=-4a +6ab+7 2B=-4a +12ab+14 A=7a -7ab-2B=7a -7ab-(-4a +12ab+14) =7a -7ab+4a -12ab-14 =11a -19ab-14 ..
A=B,B=7,所以A=7。
你的题目可能错了。
估计原题为:---------已知:A-B=7a²-7ab,且B=-4a²+6ab-7.则A=( ).
解:A-B=7a²-7ab.
所以,A=(7a²-7ab)+B=(7a²-7ab)+(-4a²+6ab-7)=3a²-ab-7.